Nutritional and Health Benefits of the Brown Seaweed Himanthalia elongata - Ilyas, Zahra; Redha, Ali Ali; Wu, Yuan Seng *; Fathima, Zahraa Ozeer; Aluko, Rotimi E. (Springer, 2023)
Himanthalia elongata is a brown seaweed containing several nutritional compounds and bioactive substances including antioxidants, dietary fibre, vitamins, fatty acids, amino acids, and macro- and trace- elements. A variety of bioactive compounds including phlorotannins, flavonoids, dietary fucoxanthin, hydroxybenzoic acid, hydroxycinnamic acid, polyphenols and carotenoids are also present in this seaweed. Multiple comparative studies were carried out between different seaweed species, wherein H. elongata was determined to exhibit high antioxidant capacity, total phenolic content, fucose content and potassium concentrations compared to other species. H. elongata extracts have also shown promising anti-hyperglycaemic and neuroprotective activities. H. elongata is being studied for its potential industrial food applications. In new meat product formulations, it lowered sodium content, improved phytochemical and fiber content in beef patties, improved properties of meat gel/emulsion systems, firmer and tougher with improved water and fat binding properties. This narrative review provides a comprehensive overview of the nutritional composition, bioactive properties, and food applications of H. elongata.